Protective role of remote ischemic conditioning in renal transplantation and partial nephrectomy: A systematic review and meta-analysis of randomized controlled trials - Zhang, Wenfu; Wu, Yingting; Zeng, Mingwang; Yang, Chao; Qiu, Zhengang; Liu, Rongrong; Wang, Lifeng; Zhong, Maolin; Chen, Qiaoling; Liang, Weidong (Frontiers in Surgery, 2023)
Objective: Studies have shown that remote ischemic conditioning (RIC)can effectively attenuate ischemic-reperfusion injury in the heart and brain, but the effect on ischemic-reperfusion injury in patients with kidney transplantation or partial nephrectomy remains controversial. The main objective of this meta-analysis was to investigate whether RIC provides renal protection after renal ischemia-reperfusion injury in patients undergoing kidney transplantation or partial nephrectomy. Methods: A computer-based search was conducted to retrieve relevant publications from the PubMed database, the Embase database, the Cochrane Library and the Web of Science database. We then conducted a meta-analysis of randomized controlled trials that met our study inclusion criteria. Results: Eleven eligible studies included a total of 1145 patients with kidney transplantation or partial nephrectomy for meta-analysis, among whom 576 patients were randomly assigned to the RIC group and the remaining 569 to the control group. The 3-month eGFR was improved in the RIC group, which was statistically significant between the two groups (P=0.02; 95% confidence inteval [CI]: 0.31 to 4.47), and the 7-day Scr levels in the RIC group decreased, which was statistically significant between the two groups (P<0.001; 95% CI: -1.74 to 4.74), but in others times, there was no significant difference between the two groups in Scr levels. The incidence of delayed graft function (DGF) decreased, but there was no significant difference (P=0.60; 95% CI: 0.67 to 1.26). There was no significant difference between the two groups in terms of operation time, cold ischemia time, warm ischemic time, acute rejection (AR), graft loss or length of hospital stay. Conclusions: Our meta-analysis showed that remote ischemia conditioning improved the estimated glomerular filtration rate (eGFR) and attenuated the renal ischemia-reperfusion injury to some extent, but cannot reduced serum creatinine (Scr), except at 7 days postoperatively. Due to heterogeneity among studies and small sample sizes, more studies and meta-analyses using stricter inclusion criteria are needed to elucidate the nephroprotective effect of RIC in renal surgery in the future.